2019
DOI: 10.1111/tpj.14350
|View full text |Cite
|
Sign up to set email alerts
|

Wheat ms5 male‐sterility is induced by recessive homoeologous A and D genome non‐specific lipid transfer proteins

Abstract: Summary Nuclear male‐sterile mutants with non‐conditional, recessive and strictly monogenic inheritance are useful for both hybrid and conventional breeding systems, and have long been a research focus for many crops. In allohexaploid wheat, however, genic redundancy results in rarity of such mutants, with the ethyl methanesulfonate‐induced mutant ms5 among the few reported to date. Here, we identify TaMs5 as a glycosylphosphatidylinositol‐anchored lipid transfer protein required for normal pollen exine develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 55 publications
2
24
0
Order By: Relevance
“…In terms of protein structure, CJt020762 contains the signal peptide, plant lipid transfer protein domain, transmembrane domain, and the GPI anchor domain modification sites ( Figure 1). This structure is similar to ms1 and ms5 in wheat [28][29][30] . Furthermore, while the plant lipid transfer protein domain and transmembrane domain of CJt020762 may be necessary for pollen production in C. japonica, an analysis of mutant wheat revealed that both the lipid transfer protein domain and transmembrane domain of wheat ms1 were necessary for pollen production 29 .…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…In terms of protein structure, CJt020762 contains the signal peptide, plant lipid transfer protein domain, transmembrane domain, and the GPI anchor domain modification sites ( Figure 1). This structure is similar to ms1 and ms5 in wheat [28][29][30] . Furthermore, while the plant lipid transfer protein domain and transmembrane domain of CJt020762 may be necessary for pollen production in C. japonica, an analysis of mutant wheat revealed that both the lipid transfer protein domain and transmembrane domain of wheat ms1 were necessary for pollen production 29 .…”
Section: Discussionsupporting
confidence: 66%
“…The fifth and final supporting evidence stems from the functional and structural similarity of CJt020762 with wheat male-sterility genes. In wheat male-sterility (Triticum aestivum), both ms1 and ms5 possess recessive inheritance and single locus control, hence male-sterility is caused by the failure of exine development during microspore formation [27][28][29][30] . MS1 in C. japonica and ms1 and ms5 in wheat have similar male-sterility phenotypes.…”
Section: Discussionmentioning
confidence: 99%
“…Genetic studies and subsequent cloning of genes for many of these mutants has revealed these as either dominant mutations or mutations in genes with a predominant functional homeolog ( Table 1 ). ms1 and ms5 are two such recessive mutants where one genome predominantly contributes to gene function [ 25 , 27 , 31 ]. ms1a mutant was the first male sterile mutant reported in wheat [ 48 ].…”
Section: Sporophytic Genes Involved In Anther and Pollen Development In Wheatmentioning
confidence: 99%
“…There are seven alleles on Ms1 locus: ms1a, ms1b, ms1c, ms1d, ms1e, ms1f, and ms1g [23,24]. Three genes-Ms1, Ms2, and Ms5-have been cloned; Ms1 and Ms5 encode a glycosylphosphatidylinositol (GPI)-anchored lipid transfer protein and Ms2 encodes an orphan protein [25][26][27][28]. The Ms1 is required for microgametogenesis in wheat.…”
mentioning
confidence: 99%
“…Knockout of Ms1 generates male-sterile lines [29]. Wheat ms5 male sterility is induced by recessive homoeologous A and D genome non-specific lipid transfer proteins [28]. Only the Ms2 mutant is currently widely used in wheat breeding [27].…”
mentioning
confidence: 99%